Magnetic titanium dioxide based nanomaterials: synthesis, characteristics, and photocatalytic application in pollutant degradation - Yao, Hongbao; Fan, Maohong; Wang, Yujun; Luo, Guangsheng; Fei, Weiyang (Journal of materials chemistry. A, Materials for energy and sustainability, 2015)
Magnetic titanium dioxide based nanocomposites have been gaining increasingly high attention in sustainable environmental protection fields; these materials can integrate the advantages of magnetic recovery and the superior photocatalysis performance of titanium dioxide. However, direct contact between crystalline photoactive titanium dioxide and magnetic iron oxide gives rise to lower photoreactivity than pure titanium dioxide for the pollutant degradation. To overcome the challenge, a number of researches have been done and significant process has been made in this area in recent years. This review primarily focuses on the properties of magnetic particles, structural models, preparation methods and techniques to improve photocatalytic performance of magnetic titanium dioxide based photocatalysts, and aims to provide a systematic overview of the current knowledge of these subjects. Notably, the recently discovered technique coupling graphene into magnetic iron oxide-titanium dioxide system is discussed, which opens a promising future for preparation of magnetic semiconductors with excellent properties. Current challenges and prospects are also proposed at the end of this article. In particular, the examination of corresponding deactivation or regeneration mechanisms should be investigated further, from the point of view of practical applications. Recent advances in synthesis methods, structure and enhanced photoactivity of magnetic titanium dioxide based photocatalysts are highlighted in this review.